2014
DOI: 10.3109/00498254.2014.942409
|View full text |Cite
|
Sign up to set email alerts
|

The comparative disposition and metabolism of dolutegravir, a potent HIV-1 integrase inhibitor, in mice, rats, and monkeys

Abstract: 1. Plasma clearance of dolutegravir, an unboosted HIV-1 integrase inhibitor, was low in rat and monkey (0.23 and 2.12 mL/min/kg, respectively) as was the volume of distribution (0.1 and 0.28 L/kg, respectively) with terminal elimination half-life approximately 6 h. Dolutegravir was rapidly absorbed from oral solution with a high bioavailability in rat and monkey (75.6 and 87.0% respectively), but solubility or dissolution rate limited when administered as suspension. 2. Dolutegravir was highly bound (>99%) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…For this analysis, animal lung concentration data were available for anidulafungin (rat), bazedoxifene (rat), chloroquine (3 albino rat studies), favipiravir (monkey), hydroxychloroquine (2 albino rat studies), nitazoxanide (mouse), tamoxifen (rat), cyclosporine (rat), ritonavir (rat), azithromycin (mouse), dolutegravir (mouse), gilteritinib (albino rat), and lopinavir (rat). [23][24][25][26][27][28][29][30][31][32] Agreement between the predicted and measured K p was assessed by simple linear regression and by constructing Bland-Altman plots, the limits of agreement (mean ± 2 SD) were included in these plots as previously described. 33…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…For this analysis, animal lung concentration data were available for anidulafungin (rat), bazedoxifene (rat), chloroquine (3 albino rat studies), favipiravir (monkey), hydroxychloroquine (2 albino rat studies), nitazoxanide (mouse), tamoxifen (rat), cyclosporine (rat), ritonavir (rat), azithromycin (mouse), dolutegravir (mouse), gilteritinib (albino rat), and lopinavir (rat). [23][24][25][26][27][28][29][30][31][32] Agreement between the predicted and measured K p was assessed by simple linear regression and by constructing Bland-Altman plots, the limits of agreement (mean ± 2 SD) were included in these plots as previously described. 33…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…Dolutegravir, an alternative drug to efavirenz or nevirapine in adult first-line ART, although primarily metabolized by UGT, is partially metabolized by CYP3A4/5 (Moss et al, 2015). Although the impact of clofazimine on UTG is not well established, a DTG area under the AUC ratio AUCR (AUCinhibitor/AUCcontrol) of 3.0 was reported, comparable to those reported with lopinavir and other strongly inhibited antiviral agents during co-administration with clofazimine (Sangana et al, 2018).…”
Section: Art Drug Interactions With Cellular Metabolic Pathwaysmentioning
confidence: 57%
“…The current study found that CYP1A1 and 1B1-dependent production of DTG metabolites (M1 and M4) were dramatically increased in the lungs of mice treated with TCDD. Interestingly, DTG is highly distributed in the lung after DTG treatment [9]. The high pulmonary exposure to DTG together with the highly induced CYP1A1 and 1B1 in the lung of smokers will increase DTG metabolism, and therefore increase the clearance of DTG.…”
Section: Discussionmentioning
confidence: 99%
“…In a mass balance study of DTG, the predominant circulating component identified in plasma was DTG, and 31.6% and 64.0% of the administrated dose was recovered in urine and feces, respectively [8]. The most abundant metabolites of DTG were the ether glucuronide followed by a benzylic hydroxylated metabolite and its hydrolytic product [9]. UDP-glucuronosyltransferase (UGT) 1A1 and cytochrome P450 (CYP) 3A4 are the two key enzymes contributing to the ether glucuronidation and benzylic oxidation of DTG, respectively [10].…”
Section: Introductionmentioning
confidence: 99%